Interregional Migration and Graduate Earning in Malaysia - Wahab, Diana Abdul; Tey, Nai Peng; Jani, Rohana (Faculty of Economics and Administration, University of Malaya, 2020)
This paper investigated the interregional migration patterns and the effects of spatial mobility on the earnings of new graduates from Malaysian universities, utilising the 2013 Tracer Study data obtained from the Ministry of Higher Education. Several local studies using the same data source mainly dealt with issues of employability, but none have studied the effects of migration on their earnings. Some graduates pursued tertiary education away from their state of birth and settled to work in the state where they studied or relocated to work in another state. This study examined graduate migration between Klang Valley (KV) and the rest of Malaysia, which differs very much in terms of economic activities and development. The estimations of the wage equation using ordinal logit models show that migration from all other states towards Klang Valley was associated with higher starting salaries for the graduates.